Developing the multiple stress–strain creep recovery (MS-SCR) test - Elnasri, Mahmoud Masoud Hamza; Airey, Gordon; Thom, Nicholas (Springer, 2018)
While most published work from Europe has been concerned with evaluating binders’ resistance to rutting based on their stiffness (deformation resistance), work originating in the US has mainly been concerned with ranking binders based on their recoverability in a multiple stress form. This paper details the design of a new modified multiple stress–strain creep recovery (MS-SCR) test. The test is designed to evaluate binders’ rutting resistance based on two rutting resistance mechanisms: stiffness and recoverability. A preliminary investigation is presented in this paper followed by details of the design of the new modified test. A 40/60 penetration grade bitumen and bitumen-filler mastics prepared with three filler concentrations (35%, 50%, and 65% filler content by mass of mastic) were tested. In addition, two polymer modified bitumens (PMBs) using the same base bitumen type were examined for validation. Two parameters are introduced to characterise the short and long recovery in the new test. In terms of stiffness, the test allows the behaviour of binders at different stress levels and loading cycles to be studied and produces a new parameter that can quantify the degree of modification. Finally, a relationship between nonlinearity and normal force in the test was investigated.